Identification of key gene networks controlling polysaccharide accumulation in different tissues of Polygonatum cyrtonema Hua by integrating metabolic phenotypes and gene expression profiles - Chen, Longsheng; Xu, Shuwen; Liu, Yujun; Zu, Yanhong; Zhang, Fuyuan; Du, Liji; Chen, Jun; Li, Lei; Wang, Kai; Wang, Yating; Chen, Shijin; Chen, Ziping; et al. (Frontiers in Plant Science, 2022)
Plant polysaccharides, a type of important bioactive compounds, involve in multiple plant defense mechanisms, especially polysaccharides-alleviated abiotic stress has been well studied. Polygonatum cyrtonema Hua (P. cyrtonema Hua) is a medicinal and edible perennial plant that is used in traditional Chinese medicine and rich in polysaccharides. Previous studies suggested that sucrose might act as a precursor for polysaccharide biosynthesis. However, the role of sucrose metabolism and transport in mediating polysaccharide biosynthesis remains largely unknown in P. cyrtonema Hua. In this study, we investigated the polysaccharides, sucrose, glucose, and fructose contents in rhizome, stem, leaf, and flower tissues of P. cyrtonema Hua, and systemically identified the genes which associated with the sucrose metabolism and transport and polysaccharide biosynthesis pathways. Our results showed that polysaccharides were mainly accumulated in rhizome, leaf and flower. Besides, there was a positive correlation between sucrose and polysaccharide content, and a negative correlation between glucose and polysaccharide content among rhizome, stem, leaf, and flower tissues. Then, transcriptomic analyses of different tissues were performed, and differentially expressed genes related to sucrose metabolism and transport, polysaccharide biosynthesis, and transcription factors were identified. The analyses on the gene expression patterns provided novel regulatory networks for the molecular basis of high accumulation of polysaccharides, especially in rhizome tissue. Furthermore, our findings explored that polysaccharide accumulation was highly correlated with the expression levels of SUS, INV, SWEET, and PLST which mediated by bHLH, bZIP, ERF, ARF, C2H2, etc, in different tissues of P. cyrtonema Hua. Herein, this study contributes to an comprehensive understanding of the transcriptional regulation of polysaccharide accumulation and provides valuable genes involved in the tolerance to abiotic stresses in P. cyrtonema Hua.